Preparation Process Optimization of Glycolipids from Dendrobium officinale and the Difference in Antioxidant Effects Compared with Ascorbic Acid. - Long, Yan; Yang, Jiajing; Ji, Hongfei; Han, Xiao; Fan, Yuting; Dai, Keyao; Ji, Haiyu; Yu, Juan (Nutrients, 2024)
Background:Dendrobium officinale glycolipids (DOG), often left as residues after hot water extraction for polysaccharide production, are often discarded. Methods: This study investigates the optimal extraction of DOG using response surface methodology, focusing on liquid–solid ratios, ethanol concentrations, extraction temperatures, and extraction times, while preliminarily analyzing DOG's structural properties. Additionally, the differences in antioxidant effects between DOG and ascorbic acid based on intestinal flora metabolism were further evaluated. Results: The optimal parameters for DOG extraction were determined as follows: liquid–solid ratio of 20 mL/g, ethanol concentration of 70%, extraction temperature of 70 °C, and extraction time of 2.5 h, yielding 2.64 ± 0.18%. In addition, DOG was identified as a diglyceride, mainly composed of glucose, mannose, linoleic acid, 9,12,15-octadecatrienoic acid, and presented certain direct free radicals scavenging effects. In animal experiments, unlike the direct free scavenging effects of ascorbic acid, DOG increased intestinal Bacteroides acidifaciens abundance in mice, up-regulated piceatannol expression, and down-regulated 1-naphthol expression, which contributed to antioxidant effects by enhancing the activities of SOD and GSH-Px while reducing MDA content. Conclusions: DOG was a diglyceride isolated from D. officinale residues after hot water extraction, and presented strong antioxidant effects by regulating intestinal flora metabolism. These findings could promote the efficient utilization of D. officinale and support further development of DOG in functional food applications.